The Impact of Topic Characteristics and Threat on Willingness to Engage with Wikipedia Articles: Insights from Laboratory Experiments - Yenikent, Seren; Holtz, Peter; Kimmerle, Joachim (Frontiers in Psychology, 2017)
A growing body of research aims to identify the factors that motivate people to make contributions in Wikipedia. We conducted two laboratory experiments to investigate the connections between topic characteristics, perception of threat, and willingness to engage with Wikipedia articles. In Study 1 (N = 83), we examined how topic familiarity, topic controversiality, and mortality salience influenced participants’ willingness to engage with Wikipedia articles. We presented the introduction parts of 20 Wikipedia articles and asked participants to rate each article with respect to familiarity and controversiality. In addition, we experimentally manipulated participants’ level of mortality salience in terms of the amount of threat they experienced when reading the article. Participants also indicated their willingness to engage with a particular article. The results revealed that willingness to engage with a Wikipedia article was predicted by both topic familiarity and controversiality of a given article. Although mortality salience increased accessibility of death-related thoughts, it did not result in any changes in people’s willingness to work with the articles. The aim of Study 2 (N = 90) was to replicate the effects of topic characteristics by following a similar procedure. We additionally manipulated uncertainty salience by assigning participants to three experimental conditions: uncertainty salience, certainty salience, and non-salience. As expected, willingness scores were again predicted by topic familiarity and controversiality. However, the manipulation of uncertainty salience did not yield any significant results despite the emergence of negative emotional states. In sum, we demonstrated that topic characteristics were factors that substantially influenced people’s willingness to engage with Wikipedia articles whereas perceived threat was not.